2010
DOI: 10.1091/mbc.e10-02-0112
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 Is Required for Redifferentiation during Madin-Darby Canine Kidney Tubulogenesis

Abstract: Signal transducers and activators of transcription (STAT)1 is the key to the sequential control of Madin-Darby canine kidney tubulogenesis. Loss of STAT1 prevents redifferentiation. Constitutively active STAT1 is sufficient to restore cord formation but not mature lumens. These data suggest that STAT1 is necessary for the redifferentiation phase of tubulogenesis and that mature lumenogenesis requires a distinct signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Cells in chains lose the apical domain, but maintain E-cadherin at the cell surface (Pollack et al 1998). Next, chains transform into cords that are 2-3 cells thick, and this transition is regulated by STAT1 (signal transducer and activator of transcription signaling) (Pollack et al 1998;Kim et al 2010). At this step, cells regain epithelial polarity and form small lumens lined by a newly established apical surface (Pollack et al 1998).…”
Section: Dynamic Rearrangements Of Polarity Drive Epithelial Morphogementioning
confidence: 99%
“…Cells in chains lose the apical domain, but maintain E-cadherin at the cell surface (Pollack et al 1998). Next, chains transform into cords that are 2-3 cells thick, and this transition is regulated by STAT1 (signal transducer and activator of transcription signaling) (Pollack et al 1998;Kim et al 2010). At this step, cells regain epithelial polarity and form small lumens lined by a newly established apical surface (Pollack et al 1998).…”
Section: Dynamic Rearrangements Of Polarity Drive Epithelial Morphogementioning
confidence: 99%
“…MDCK cysts were grown in 3D Matrigel or collagen I cultures (BD Biosciences, Sigma) (Bryant et al, 2010;Kim et al, 2010). For tubulogenesis, the Matrigel overlay was removed on day 4 by 0.25% trypsin and overlaid with collagen.…”
Section: D Cultures and Tubulogenesismentioning
confidence: 99%
“…Immunofluorescence, microscopy and image analysis Cyst or tubule were fixed and processed for immunohistochemistry as previously described (Kim et al, 2010). Primary antibodies were against: β-catenin (Santa Cruz Biotechnology, catalog number sc-7199), myosin IIA (Covance, catalog number PRB-440P), E-cadherin (BD Biosciences, catalog number 610181), ZO-1 (gift of Bruce Stevenson, Department of Cell Biology and Anatomy, University of Alberta, Canada), phosphorylated ERM (Chemicon, catalog number AB3832), PODXL (George Ojakian, Department of Anatomy and Cell Biology, State University of New York, NY), and secondary antibodies conjugated with Alexa Fluor 488 or 568 (Molecular Probes) and Hoechst 33342 (Molecular Probes) were used.…”
Section: Dna Constructs and Lentivirus Infectionmentioning
confidence: 99%
“…In vitro experiments with embryonic kidney explants suggested that STAT1 activation plays a pro-proliferative role in metanephric mesenchymal cells, and antagonizes epithelial differentiation and tubulogenesis 41 . Experiments with MDCK cells as a model of in vitro tubulogenesis yielded conflicting results and suggested that STAT1 is required for tubulogenesis 43 . Given that STAT1 null mice do not exhibit a defect in renal development 41 , 44 , 45 it is currently difficult to reconcile these studies or assign any definite role for STAT1 specifically in the kidney (besides its ubiquitous roles during immune responses and inflammation).…”
Section: What Is the Normal Role Of Stats In The Kidney?mentioning
confidence: 99%